Synthesis of Surfactant-Modified Activated Carbon (SMAC) Above Critical Micelle Concentration as Cr(VI) Ion Adsorbent - Arnelli Arnelli; Sri Guswini; Ahmad Suseno (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
The synthesis of surfactant-modified activated carbon (SMAC) has been widely studied. However, no research has been conducted to study SMAC concentrations higher than the critical micellar concentration. Therefore, in this study, SMAC was synthesized using anionic and cationic surfactants above CMC (Critical Micelle Concentration) and compared with SMAC below CMC and coconut husk-based activated carbon. This study aimed to determine the surface profile of SMAC and the characteristics and mechanism of metal ion adsorption by SMAC. The selected metal ions were Cr(VI) cations and NH4+ cations as a reference. SMAC was prepared by modifying coconut shell-based activated carbon with anionic surfactant SLS (Sodium Lauryl Sulfate) and cationic surfactant HDTMA-Br (Hexadecyl Trimethyl Ammonium Bromide). Modification of SMAC was performed by three different methods: (a) activated carbon was added gradually with SLS followed by HDTMA-Br, (b) activated carbon was added with HDTMA-Br followed by SLS, (c) activated carbon was mixed with SLS and HDTMA-Br simultaneously. All synthesized SMAC were characterized using FTIR, GSA (Gas Sorption Analyzer), and zeta potential. The FTIR analysis results showed that the synthesized SMAC comprised S=O and (CH3)3N+ groups derived from surfactants. GSA analysis revealed that SMAC has a surface area of 36.790 m2/g, and it was more stable than activated carbon according to the zeta potential result. In this study, the efficiency of SLS and HDTMA-Br in synthesizing SMAC was 99.98% and 95.85%, respectively. SMAC synthesis using method c resulted in Cr(VI) adsorption efficiency of 93.50% and NH4+ adsorption efficiency of 87.37%. In comparison, SMAC below CMC has adsorption capacities of 93.41% for Cr(VI) and 85.05% for NH4+, respectively, whereas Cr(VI) adsorption efficiency by coconut shell-based activated carbon was 99.98%.